2016
DOI: 10.4103/1793-5482.175632
|View full text |Cite
|
Sign up to set email alerts
|

Acute subdural hematoma secondary to cerebral venous sinus thrombosis: Case report and review of literature

Abstract: Cerebral venous sinus thrombosis is a rare type of stroke primarily affecting young women. Diagnosis is generally delayed or overlooked due to a wide spectrum of clinical symptoms. Subdural hematoma secondary to cerebral venous sinus thrombosis is very rare. We report a case of 40-year-old female with cerebral venous sinus thrombosis who presented to us with an acute subdural hematoma and subarachnoid hemorrhage besides venous infarct. Management of such patients is complicated due to the rarity of the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Currently, the combination of MRI and MRV has largely replaced the minimally invasive cerebral angiography and CT diagnosis, becoming the gold standard of CVT. [ 1 , 18 ] In this patient, there were no significant abnormalities in the early CT examination. Then, the MRI combined with MRV indicated that the flow void signal of superior sagittal sinus and left transverse sinus disappeared, and irregular filling defect appeared.…”
Section: Discussionmentioning
confidence: 64%
“…Currently, the combination of MRI and MRV has largely replaced the minimally invasive cerebral angiography and CT diagnosis, becoming the gold standard of CVT. [ 1 , 18 ] In this patient, there were no significant abnormalities in the early CT examination. Then, the MRI combined with MRV indicated that the flow void signal of superior sagittal sinus and left transverse sinus disappeared, and irregular filling defect appeared.…”
Section: Discussionmentioning
confidence: 64%
“…The literature until recently was restricted to isolated case reports and case series. 7 In a retrospective multicenter cohort study of 260 patients with confirmed CVST over a period of 15 years in Mexico and Europe, the incidence of such SDH was reported to be 11%. 12 SDH can be isolated or may occur together with other types of intracranial hemorrhages and there are no clinical features which are specific to SDH.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Subdural hemorrhage (SDH) as a complication of CVST is even rarer and can easily be overlooked. 7 The diagnosis of this is even more difficult, yet can be very rewarding if done in a timely fashion. 8 In this article, we present a middle‐aged woman whose presentation was with a worsening headache and a generalized tonic clonic seizure.…”
Section: Introductionmentioning
confidence: 99%
“…Dural AVFs have various clinical manifestations from aggressive neurological defects to no or minor symptoms and signs depending mainly on the pattern of abnormal drainage of the veins. 1) Classification systems which are based on its mode of venous flow are used in cases of DAVF to estimate hemorrhage risks and to decide management strategies. 4) Intracranial hemorrhage occurs in less than 20% of all these pathologies, and the bleeding is usually subarachnoid, more infrequently intra-parenchymal, and rarely in the subdural space.…”
Section: Discussionmentioning
confidence: 99%